INFLUENCE OF POISON COMPOUNDS UPON THE ACTIVITY OF MONO AND BE-METALLIC REFORMER CATALYSTS - A.S. Nasution (Scientific Contributions Oil and Gas, 1983)
Caelyie neforming proces ses a bunctional catals. Annperimen ha been carried ourt study he inluence of phur, nangen, oxygeneand lead com pound upon ihe activity of the metal sine of muno and beetale refarmer curalys ing Adrogenation of benone continous cetates anit.